Validity and reliability: teachers’ pedagogical instrument for identifying sensory-motor abilities in handwriting readiness - Hanum Hanifa Sukma; Muhammad Ragil Kurniawan; Mukti Sintawati; Sadiki Moshi Feruzi; Satrianawati Satrianawati (International Journal of Evaluation and Research in Education (IJERE), 2025)
The teacher’s ability to identify students’ sensory motor skills is very important. Sensory motor skills are the foundation for children’s handwriting skills. However, there is no instrument to measure teachers’ abilities in this regard. This study aims to test the validity and reliability of the instrument measuring teachers’ pedagogical knowledge in identifying students’ sensory-motor abilities. The data was collected using a questionnaire. A total of 552 teachers responded to the survey. The data were analyzed using exploratory factor analysis (EFA). The study results have developed a questionnaire with four construct components with 39 items. All four constructs have a high-reliability index. The EFA analysis indicated that all items were accepted with high agreement. The results prove that the instrument is highly valid and reliable. Based on the test results, this instrument is recommended for measuring pedagogical knowledge teachers in identifying sensory-motor abilities for elementary school students’ handwriting readiness. The measurement results can be used to determine appropriate training for teachers in developing the sensory-motor abilities of elementary school students. The innovation of this research is the development and validation of an instrument that can measure teachers’ pedagogical knowledge in identifying the sensorimotor abilities of elementary school students.